A technical note investigating the combination boiler market as a proxy for a simple thermal quality of service standard in heat interface units. (September 2019) - Blackwell, Huw
Heat interface units used in district heating networks provide very similar services to those expected from domestic gas boilers. As heat interface units become more common, it is becoming clear that heat interface units are often oversized. This technical note aims to review and summarise the technical specification of equipment typically available from combination boiler (also known as combi boilers) manufacturers in the UK. This includes thermal outputs and flow rate limitations, particularly those associated with domestic hot water production. It is proposed for use as an equivalent typical minimum domestic hot water flow rate and maximum thermal power benchmark for domestic hot water production by heat interface units, which are utilised in the equivalent role in the communal and district heating market. The aim is to prevent extensive oversizing of heat interface units, thereby reducing capital costs, pipe sizes and improving efficiency on district and communal heating networks. Practical application: This technical note proposes a DHW quality of service standard based on a review of the UK heating system market (specifically the combination boiler market) and water consumption restrictions arising from Building Regulations. This may be used to define an equivalent maximum thermal power and minimum service flow rate when specifying heat interface units used in residential communal heating systems and district heating systems.